Southwestern Atlantic species of conoidean gastropods of the genus Aforia Dall, 1889 - Pastorino, Guido; Sánchez, Noelia (Zootaxa, 2016)
A new species of the conoidean genus Aforia is described from the Southwestern Atlantic in Argentine deep waters. Detailed study of the type material of nominal species, Aforia goniodes (Watson, 1881) and its synonym Pleurotoma clara Martens, 1880, both described from deep waters off Argentina, allowed recognition of a new species. Aforia obesa sp. nov. was collected from 7 stations in 647 to 1,398 m depth during three cruises to the Mar del Plata submarine Canyon in the Argentine continental slope on the R/V “Puerto Deseado”. Shells, radulae, penises and opercula of adults and juveniles of A. obesa n. sp. from several localities are illustrated, described and compared to other living congeners.